(untitled) - Borstlap, C. J.

The lignocellulose degrading capability of Coniochaeta pulveracea CAB 683: an omics approach (Stellenbosch : Stellenbosch University, 2022)
Thesis (MSc)--Stellenbosch University, 2022.